Extreme child poverty and the role of social policy in the united states. (28th February 2019) - Parolin, Zachary; Brady, David
Abstract : This paper applies improved household income data to reevaluate the levels, trends, composition, and role of social policy in extreme child poverty in the US from 1997 to 2015. We adjust for benefit underreporting and incorporate the Supplemental Nutritional Assistance Program (SNAP). This reduces the share of children below 2 per day from 1.8 per cent to 0.1 per cent in 2015. However, survey data omits the 1.3 million homeless children. Unlike prior literature's focus on single motherhood, citizenship status is more consequential to extreme poverty. We also demonstrate that increases in SNAP generosity and take-up enabled declines in three measures of extreme child poverty.